ANALISIS KADAR UNSUR HARA PADA KOMPOS DARI BATANG PISANG KEPOK (Musa acuminata) DENGAN AKTIVATOR EM4 DAN AIR CUCIAN BERAS - Alfarestu, Rifqi; Muhelni, Leila; Anwar, Hendra (Smart Education, 2025)
Abstract: Kepok banana (Musa acuminata) stem waste was mixed with rice bran to make compost, aiming to return organic matter to the soil and increase fertility. This study examined the effectiveness of EM4 activator and rice washing water in composting banana stem waste. There were four treatments: banana stem, bran (BD), banana stem, bran, rice washing water (BDA), banana stem, bran, EM4 (BDE), and banana stem, bran, EM4 and rice washing water (BDAE). The results showed that the addition of EM4 and rice washing water increased the composting speed within 30 days, using a C/N ratio reaching 20.76%, according to SNI standards. The nutrient content of the compost also met SNI 19-7030-2004 standards, using analysis providing levels of Nitrogen, Phosphorus, Potassium, organic C, and water content suitable for use. This study recommends further development to produce Liquid Organic Fertilizer (POC).Keyword: Analysis of Nutrient Content in Compost from Kepok Banana Stems (Musa acuminata) with EM4 Activator and Rice Washing Water.Abstrak: Limbah batang pisang kepok (Musa acuminata) dicampur memakai dedak untuk dibuat kompos, bertujuan mengembalikan bahan organik ke tanah serta menaikkan kesuburan. Penelitian ini melihat efektivitas aktivator EM4 serta air cucian beras dalam pengomposan limbah batang pisang. Terdapat empat perlakuan: batang pisang, Dedak (BD), batang pisang, Dedak, Air cucian beras (BDA), batang pisang, Dedak, EM4 (BDE), dan batang pisang, Dedak, EM4 dan Air cucian beras (BDAE). Akibat menyampaikan bahwa penambahan EM4 dan air cucian beras meningkatkan kecepatan pengomposan pada waktu 30 hari, memakai rasio C/N mencapai 20,76%, sesuai standar SNI. Kandungan hara pada kompos juga memenuhi standar SNI 19-7030-2004, memakai analisis membagikan kadar Nitrogen, Fosfor, Kalium, C organik, dan kadar air yang layak digunakan. Penelitian ini merekomendasikan pengembangan lebih lanjut buat menghasilkan Pupuk Organik Cair (POC).Kata kunci: Analisis Kadar Unsur Hara Pada Kompos Dari Batang Pisang Kepok (Musa acuminata) Dengan Ativator EM4 Dan Air Cucian Beras.